Segregation in action: The exclusion of aboriginal children from the school at Nambucca Heads (NSW, 1915) (2009)
This article focuses on a redefining moment of racial frontiers in the small town of Nambucca Heads on the north coast of New South Wales, in the southeast of Australia: the process of segregation of the school in 1915. The careful analysis of all the facets of this event (and in particular of the various forms of 'indigenous reactions') will enable us to question the conditions of emergence of discriminating patterns between Blacks and White, which didn't exist until then.